Household latrine utilization and its association with educational status of household heads in Ethiopia: a systematic review and meta-analysis - Cheru Tesema Leshargie; Animut Alebel; Ayenew Negesse; Getachew Mengistu; Amsalu Taye Wondemagegn; Henok Mulugeta; Bekele Tesfaye; Nakachew Mekonnen Alamirew; Fasil Wagnew; Yihalem Abebe Belay; Aster Ferede; Mezinew Sintayehu; et al. (BMC, 2018)
Abstract Background Ethiopia has been experiencing a high prevalence of communicable diseases, which resulted in high morbidity, mortality, and hospital admission rates. One of the highest contributing factors for this is lower level of latrine utilization. There had been significantly varying finding reports with regard to the level of latrine utilization and its association with education level from different pocket studies in the country. Therefore, this systematic review and meta-analysis was aimed to estimate the pooled prevalence of household latrine utilization and its association with education status of household heads, in Ethiopia using available studies. Methods This systematic review and meta-analysis was conducted using available data from the international databases, including PubMed, Google Scholar, Science direct, Cochrane library and unpublished reports. All observational studies reporting the prevalence of latrine utilization in Ethiopia were included. Four authors independently extracted all necessary data using a standardized data extraction format. STATA 13 statistical software was used to analyze the data. The Cochrane Q test statistics and I 2 test were used to assess the heterogeneity between the studies. A random effect model was computed to estimate the pooled level of latrine utilization in Ethiopia. In addition, the association between latrine utilization and the educational level of the users was analyzed. Results After reviewing of 1608 studies, 17 studies were finally included in our meta-analysis. The result of 16 studies revealed that the pooled prevalence of latrine utilization level in Ethiopia was 50.02% (95%CI: 40.23, 59.81%). The highest level (67.4%) of latrine utilization was reported from Southern Nations Nationality and People regional state, followed by Amhara regional state (50.1%). Participants who completed their high school and above education were more likely (OR: 1.79, 95%CI: 1.05, 3.05) to utilize latrine compared to those who did not attend formal education. Conclusion In Ethiopia, only half of the households utilize latrine and the level of utilization has significant association with educational status.